IMPLEMENTASI PERATURAN DAERAH NO.7 TAHUN 2009 TENTANG PENYELENGGARAAN ADMINISTRASI KEPENDUDUKAN KABUPATEN SEMARANG (STUDI KASUS PADA PENCATATAN KELAHIRAN DAN PENERBITAN AKTA KELAHIRAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SEMARANG) - Adhikaputra, Harwindo; Hidayat, Zainal; Mustam, Mochmad (Journal of Public Policy and Management Review, 2015)
Various problems such as lack of public awareness of the Semarang District particular demographic data ownership birth certificate into the background of this research. This study aims to determine how the implementation of Semarang District Regulation No.7 of 2009 on Population Administration in Semarang district and identify factors driving and inhibiting in the implementation of the registration and recording of population. This study uses descriptive qualitative research methods. The subjects in this study consists of six (6) key informants.The results showed that the implementation of Semarang District Regulation No.7 of 2009 on Population Administration shows that walking good implementation. But Less Her amount of resources to be a problem that must be faced by the Department of Population and Civil Registration Semarang district in providing services to the public, as well as the transitional administration system administration manual to computer systems that have not been synchronized, causing inaccuracies in the data has. And the lack of public awareness that has been aged for ownership of population data to itself.Based on these conclusions, the researchers recommend to the executive population registration and civil registration in order to encourage dissemination to the public to register themselves in the Department of Population and Civil Registration Semarang district and implementing e-government in the implementation of the settlement administration.